Ductile Fracture of Steel Sheets under Dynamic Membrane Loading. (2017) - Gruben, Gaute; Morin, David; Langseth, Magnus; Hopperstad, Odd S.
Abstract: Failure prediction assessment is conducted based on validated finite element simulations of impact tests performed on 1.8 mm dual-phase and 1.0 mm martensitic steel sheets. The sheets were clamped between two steel rings and subjected to lateral loading by a punch with a hemispherical nose. Three different specimen geometries were applied. These were chosen to provide membrane loading in stress states near uniaxial tension, plane-strain tension and equi-biaxial tension. Thus, the most important stress states that may occur for thin sheets in an impact situation are covered. Finite element simulations of the impact tests are run with the nonlinear code LS-DYNA. The plastic behaviour of the materials is modelled using the Hershey yield function in combination with the associated flow rule and isotropic hardening. The specimens are discretized by shell elements, thus imposing a state of plane stress. Three different approaches for modelling ductile failure are evaluated by comparing the experimental and simulated force-displacement curves from the experiments on the two steel materials.